Research of Factors which influence Success of ERP Solutions Use - Sternad Zabukovšek, Simona; Bobek, Samo (Naše gospodarstvo/Our economy, 2014)
Enterprise resource planning (ERP) solutions are critical IS for today’s organizati- ons. They solve problems related to information integration from different sources of the organization’s environment in real time for all of its employees and partners. However, ERP solutions bring organizations benefits only to the extent to which users adopt and use them in their daily work. In order to improve the efficiency and effectiveness of ERP solutions, organizations need to explore the factors that influen- ce customer satisfaction. Among the models that focus on users’ behavioral aspects and examine those factors that influence the successful adoption and use of IT/IS, the most widely used model is the technology acceptance model (TAM). Therefore, we investigated the use of TAM in conjunction with ERP solutions.